PENELUSURAN SENYAWA BIOAKTIF BAKTERI YANG BERASOSIASI DENGAN ANEMON LAUT SERTA IDENTIFIKASI MOLEKULERNYA BERBASIS 16S rDNA - Naely K Wusqy; Dwi I Prayitmo; Ocky K Radjasa; Leenawaty Limantara; Ferry F Karwur1 (Jurnal Perikanan Universitas Gadjah Mada, 2012)
Sea anemone-associated microorganisms are among of the most interesting and promising marine natural product sources, which produce various biological activities. In this study, marine bacteria were isolated from 2 kinds of sea anemones, Entacmaea medusivora and Green Anemone that were collected from Bandengan, Jepara and Maratua, East Borneo respectively. Nine bacterial isolatesof E.medusivora were screened for antibacterial activity against 8 strains. One out of 9 bacterial isolates was successfully screened and was found to be active against V. parahaemolyticus strains. This active isolate was also capable of amplifying PKS gene fragments necessary for the biosynthesis of polyketide synthase. The identiﬁ cation results revealed that the active isolate is Bacillus cereus. One bacterial isolate of Green Anemone was screened to produce the pigment and positively synthesize carotenoids. Initial analysis with atomic absorption spectrophotometric method revealed that the wave length of bacterial pigment were in the range of 300-600 nm, which are categorized that within the group of carotenoid pigments. From the results of molecular identiﬁ cation by 16S rDNA method, it was shown that bacterium was closely related to Xanthomonas sp.